Arabidopsis BSL phosphatases regulate zygote polarity through a brassinosteroid-independent essential function in MAP kinase signaling - Sangho Jeong; Gabriel Eschedor; Magdy Alabady; Wolfgang Lukowitz (Proceedings of the National Academy of Sciences, 2026)
The main axis of the plant body is established in early embryogenesis. Polar growth and asymmetric division of the Arabidopsis zygote require the Mitogen-Activated Protein (MAP) kinase kinase kinase YODA and the MAP kinases MPK3/MPK6, but regulation of this signaling cascade is not well understood. Here, we show that three BSU1-LIKE phosphatases (BSL1-3) are essential positive regulators: A combined loss causes closely similar defects to loss of the YODA MAP kinase cascade, resulting in nonpolar embryos; transcriptional profiling and cell-fate markers confirm that BSL phosphatases and the MAP kinase cascade regulate the same process. Unexpectedly, the founding member of the family, BSU1, appears dispensable. These results cast doubt on the view of BSU1-family phosphatases as core components of brassinosteroid hormone signaling. MPK3 activity shows striking sensitivity to BSL dosage, and genetic interactions with activated MPK3 suggest that BSL phosphatases function downstream of YODA and either in conjunction with or downstream of MPK3/MPK6, implying a novel mechanism of MPK regulation.